Adrenal Gland Microenvironment and Its Involvement in the Regulation of Stress-Induced Hormone Secretion during Sepsis - Kanczkowski, Waldemar; Sue, Mariko; Bornstein, Stefan R. (Frontiers in Endocrinology, 2016)
Survival of all living organisms depends on maintenance of a steady state of homeostasis, which process relies on its ability to react and adapt to various physical and emotional threats. The defense against stress is executed by the hypothalamic-pituitary-adrenal axis and the sympathetic-adrenal medullary system. Adrenal gland is a major effector organ of stress system. During stress adrenal gland rapidly respond with increased secretion of glucocorticoids and catecholamines into circulation, which hormones, in turn, affect metabolism, to provide acutely energy, vasculature to increase blood pressure and the immune system to prevent it from extensive activation. Sepsis resulting from microbial infections is a sustained and extreme example of stress situation. In many critical ill patients levels of both corticotropin-releasing hormone and adrenocorticotropin, two major regulators of adrenal hormone production, are suppressed. Levels of glucocorticoids however, remain normal or are elevated in these patients, suggesting a shift from central to local intraadrenal regulation of adrenal stress response. Among many mechanisms potentially involved in this process, reduced glucocorticoid metabolism and local intraadrenal activation of hormone production mediated by adrenocortical and chromaffin cell interactions, the adrenal vascular system and the immune-adrenal crosstalk play a key role. Consequently, any impairment in function of these systems, can ultimately affect adrenal stress response. The purpose of this mini review is to present and discuss recent advances in our understanding of the adrenal gland microenvironment, and its role in regulation of stress-induced hormone secretion.